2014
DOI: 10.1097/cco.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Neural network alterations underlie cognitive deficits in brain tumor patients

Abstract: Cognitive deficits in brain tumor patients are reflected in whole-brain network disturbances. Possible future clinical use of these findings mostly concerns prognostics and tailoring treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
4
47
0
Order By: Relevance
“…This slow‐wave oscillatory activity has been observed both within and between brain regions (Bajo et al, ; Dunkley et al, ; Hier et al, ). Furthermore, our findings of increased FC strength scores in PBT children are consistent with previous resting‐state research conducted in adult brain tumor survivors showing increased low frequency FC (Bartolomei et al, , ; Bosma et al, ; Derks, Reijneveld, & Douw, ). We have previously shown that PBT survivors display greater resting‐state theta power compared with healthy children (Dockstader et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…This slow‐wave oscillatory activity has been observed both within and between brain regions (Bajo et al, ; Dunkley et al, ; Hier et al, ). Furthermore, our findings of increased FC strength scores in PBT children are consistent with previous resting‐state research conducted in adult brain tumor survivors showing increased low frequency FC (Bartolomei et al, , ; Bosma et al, ; Derks, Reijneveld, & Douw, ). We have previously shown that PBT survivors display greater resting‐state theta power compared with healthy children (Dockstader et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…In particular, four cognitive domains were examined that have been identified by previous studies to be affected by brain tumors: sustained attention, working memory, information processing speed, and executive functioning (Derks et al, 2014). One glioma patient was not tested because of lack of time, and one meningioma patient did not complete the sustained attention task.…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment of homologous language-related areas in the contralesional cerebral hemisphere has been extensively verified in stroke and glioma patients (Desmurget et al, 2007;Duffau 2014;Thiel et al, 2005;Winhuisen et al, 2005;Yang et al, 2016). The second interpretation is to view the increased RSFC between network regions (i.e., hyperconnectivity) as a fundamental response to neurological disruption in patients with focal lesions or neurodegenerative/psychiatric diseases (Derks et al, 2014;Hillary & Grafman, 2017;Hillary et al, 2015). For example, SFG and MFG in the dominant hemisphere are charged with higher-order cognitive control, whereas dominant AG and IPL primarily undertake the role of linguistic comprehension (Fedorenko & Thompson-Schill, 2014;Wu et al, 2015).…”
Section: Alteration Of Cerebro-cerebellar Functional Connectivitymentioning
confidence: 98%
“…However, the neural mechanisms underlying cognitive impairments in glioma patients are largely unclear (Derks et al, 2017;Derks, Reijneveld, & Douw, 2014). However, the neural mechanisms underlying cognitive impairments in glioma patients are largely unclear (Derks et al, 2017;Derks, Reijneveld, & Douw, 2014).…”
Section: Introductionmentioning
confidence: 99%